What is the evidence for clinical use of advanced technology in unicompartmental knee arthroplasty?. Issue 5 (30th June 2021) - Mittal, Anurag; Meshram, Prashant; Kim, Tae Kyun
Abstract: Background: With an aim of improving prosthesis survivorship of unicompartmental knee arthroplasty (UKA), use of computer‐assisted technologies (CATs) such as robotics, has been on the rise to reduce intraoperative errors in surgical technique. In light of recent influx of CATs in the UKA, a review of these innovations will help providers to understand their clinical utility. Method: A systematic literature search was performed following Preferred Reporting Items for Systematic Review and Meta‐Analysis guidelines. Results: Among 19 studies comparing robot‐assisted UKA with conventional UKA, only 32% were randomized control trials, 47% reported minimum mean follow‐up of 2 years, and 21% evaluated prosthesis survival. Similar results were obtained for navigation‐assisted UKA and UKA performed with patient‐specific instrumentation. Conclusion: While CATs seem to reduce the surgical errors in UKA, the evidence on the efficacy of any of the studied CATs to improve survivorship remains limited and there are issues related to cost‐effectiveness, learning curve, and increase in operating time.